Effects of Promotion, Training and Compensation on Employee Retention in Commercial Banks in Nepal - Shakya, Sonila (The Gaze: Journal of Tourism and Hospitality, 2024)
Employees are a company’s enormous asset and are crucial to its competitiveness and successful operation. Today, most of the organizations struggle to manage and retain their employees. This study aims to examine the relationship between promotion, training, and compensation, as well as the impact of these factors on employee retention in commercial banks in the context of Nepal. A cross-sectional research design was undertaken to determine the degree of a relationship among variables under investigation. A structured questionnaire with 5 5-point Likert scale was designed to collect the data from the population. This study used a non-probability convenience sampling technique, and data were collected from 215 employees working in A- class commercial banks who hold various hierarchical positions. For analyzing the data, the SPSS 20 version has been used to test the study model and proposed hypotheses. The results indicate a significant positive correlation between employee retention and promotion, training, and compensation. Additionally, the findings indicate that compensation significantly impacts employee retention, followed by promotion and training in commercial banks in Nepal.